Education and Mentoring on Organic Fertilizer Using PGPR Biodecomposer for Karang Taruna BABE in Bakalan, Bululawang, Malang Regency - Joko Raharjo, Sentot; In Oktavia, Anggraeni; Oktavia Rahayu, Lina (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
The existence of Minister of Agriculture Regulation Number 10 of 2022 concerning restrictions on national fertilizer subsidies among farmers requires alternative development of fertilizer processing. The aim of this Community Service is to educate and assist the BABE youth organization and residents of Bakalan village, Bululawang, Malang Regency in the Rapid Processing of Organic Fertilizer using the Plant Growth Promoting Rhizobacteria (PGPR) Biodecomposer. The method of this activity is Participatory Action Research (PAR) including a survey of the potential for rapid processing of organic fertilizer, outreach and education as well as assistance in processing it. The result of community service activities is increased knowledge and ability of the community in processing cow dung waste into organic fertilizer products with quality that complies with government regulations. The conclusion of this activity is that education and mentoring to youth organizations and residents of Bakalan village, Bululawang, Malang Regency can increase the knowledge and skills of village residents in the production of Rapid Processing of Organic Fertilizer Using PGPR.